Produção dos artefatos de couro em Ipirá-BA: estratégias educacionais para a conscientização sócio-ambiental e ações de sustentabilidade - Santos, Lilian Cruz (2023)
This research aimed to promote educational strategies aimed at socio-environmental awareness and sustainable actions aimed at reusing solid waste from the production of leather artifacts, in the municipality of Ipirá-BA. The production of leather artifacts in the municipality of Ipirá is highlighted by the large volume of production with sales scope of companies in the municipality, covering the entire national territory. The main specialization of the artifacts hub in Ipirá is leather wallets, bags and the like, being responsible for generating more than 5 thousand direct jobs in the municipality. The reuse of solid waste from these productions could contribute to the economic development of the territory, as well as reducing the environmental impacts caused by waste from leather factories, in the region of Ipirá-BA. The work was carried out at the Colégio Estadual de Ipirá-BA , the place where I work, and which belongs to the schools of the State Public Network of Bahia, within a qualitative research methodology of the case study type developed in the region of Ipirá, Bahia, with a theme of a socio-environmental and socio-scientific nature , relevant to the school community. In search of diagnoses on the production of leather artifacts in the region, questionnaires were initially drawn up and applied to production owners and factory employees, with qualitative data analysis. After this activity, the data was tabulated, with the construction of graphs and analysis of the results. The class was subdivided into groups, which prepared questionnaires for field research and applied these questionnaires to four productions in the municipality, complying with the following criteria: each group interviewed a production with questionnaires applied to the owner and employees. As a result of this research, it was possible to encourage student protagonism through experience and interaction with the topic, based on Experimentation, Scientific Research, Mediation and Sociocultural Intervention activities, thus diversifying learning strategies. Developing educational products: research seminars, pedagogical workshop and craft fair, prepared and executed in a didactic sequence, a discussion can be promoted and raising awareness among the school community about socio-environmental issues and the reuse of solid waste from the production of leather artifacts, as well as creating an alternative source of income.